The economic impact of terrorism – the efficiency of funds allocated by international development organizations (Gaza Strip Case Study) - Luiza-Andreea ULMET (Bulletin of "Carol I" National Defense University, 2024)
Terrorism is a concept that has existed internationally since ancient times, receiving different names from specialists depending on the period in which it was identified, the means and methods used in the activities carried out or the aims pursued by the actions of the members of various organizations.One thing we would like to point out is that as long as there are different points of view, as long as the interests of some of the parties involved in a conflict, including those of an economic nature, are at odds, then the conditions will be created for the development or coagulation of resistance movements, which by their actions will be labelled as terrorist organizations.One of the main terrorist organizations causing immeasurable economic damage, and whose actions are also likely to affect international relations, is Harakat al-Muqawama al-Islamiyya – HAMAS, also known as the Islamic Resistance Movement, which since 2006 has taken control of the Gaza Strip using armed force, imposing political and economic separation from the Palestinian Authority.